(untitled) (Educational Knowledge, 2015)
There is a form of harassment among young people called cyberbullying, which consists of using Information and Communication Technologies (ICTs), specifically email, social media, and others, to harass, intimidate, and denigrate an individual or a group of people. Human aggression and bullying as a type of aggression are analyzed to understand cyberbullying. The main objective of this research was to explore how personal variables, the experience of cyberbullying, and attitudes toward violence manifest themselves in students involved in the dynamics associated with this type of social process.